Study on the impact of hometown resource endowment on farmers’ rural-urban migration decisions against the background of “dual carbon” - Gao, Ping; Shen, Suyan; Yang, Zhenyu; Ji, Zheyan (Frontiers in Environmental Science, 2024)
This study investigates the impact of hometown resource endowment on farmers’ rural-urban migration decisions within the context of “Dual Carbon” policies. It aims to understand the factors influencing migration decision-making amidst the dynamics of urban and rural land occupation, particularly focusing on the role of hometown resource endowments led by homesteads. Using data from the China Migrants Dynamic Survey (CMDS), this study analyzes the influence of hometown resource endowment, primarily residential land, on farmers’ migration decisions. Ownership of homesteads and contracted land significantly affects farmers’ settlement in cities, while the dividend effect from village collectives is negligible. Additionally, the administrative level of the hometown serves as a significant factor in migration decision-making, particularly in family migration. Homestead and contracted land ownership negatively impacts both household and individual migration decisions. Specifically, owning homesteads exerts a greater influence on whole family migration decisions, reducing the probability of settling in cities by 21.1%. Regional comparative analysis reveals varying effects of owning homesteads and contracted land. While it positively influences household migration to cities in the eastern region, it inhibits migration in the central and western regions. The findings highlight the complex interplay between hometown resource endowment, land use patterns, and rural-urban migration decisions. Understanding these dynamics is crucial for designing effective policies to address migration challenges in the context of environmental and socioeconomic transitions.